Impact of HCV cure on systemic inflammation and bone density, quality, and turnover - Psomas, Christina K.; Lellouche-Slama, Elsa; Langan, Susan; Sulkowski, Mark; Moseley, Kendall F.; Pena-Dias, Jenny; Khati, Smita; Sun, Jing; Abraham, Alison G.; Brown, Todd T. (Frontiers in Immunology, 2025)
BackgroundChronic hepatitis C virus (HCV) infection has been associated with osteoporosis and fragility fracture, which may be mediated by increased systemic inflammation, especially in HIV-HCV co-infection. Treatment with direct-acting antivirals (DAA) eradicates HCV and decreases inflammation, but the impact on bone parameters has not been studied.MethodsWe recruited individuals with HCV infection with and without HIV co-infection who initiated DAA, and a demographically matched reference group without HIV or HCV, on whom dual-energy X-ray absorptiometry (DXA) scans were performed at baseline. All participants with HCV who displayed sustained virologic response were included and underwent a follow up visit with DXA between 52 and 134 weeks after baseline to measure bone mineral density at the lumbar spine (LS), femoral neck (FN), and total hip (TH), as well as the trabecular bone score (TBS), a bone quality measure. Bone turnover markers (BTM) and inflammatory biomarkers were also measured at baseline and the follow-up visit. We compared the change in inflammatory biomarkers and bone outcomes over time between the groups.ResultsThe group with HCV (41 mono-infected, 18 people with HIV/HCV co-infection) had a median age of 54 years; 61% were male and 76% were African American. Population characteristics were similar in the reference group (n=53). At baseline, soluble receptor for TNFα 1 and 2 (sTNFR-1/sTNFR-2) and sCD163 concentrations, but not interleukin-6, were higher in participants with HCV infection compared to the reference group. After a median follow-up period of 60 weeks, HCV cure was associated with decreases in sTNFR1, sTNFR2 and sCD163 concentrations. However, we observed no statistically significant changes in BMD, TBS or BTM after HCV treatment compared to the reference population. Among those with HCV, participants with HIV co-infection showed a significant increase in the bone formation marker P1NP (p<0.007) and trends toward greater increases in LS and TH BMD (p<0.08 for both) after HCV cure.ConclusionHCV cure using DAA was associated with a decrease in systemic inflammation without changes in bone parameters. The significant increase in bone formation markers observed in HIV/HCV co-infected individuals suggests potential bone recovery in this high-risk group, warranting investigation in larger long-term studies.